27 Metabolic Outcomes of Children and Adults Born Preterm. (October 2012) - Modi, N; Singhal, A; Fewtrell, M; Hyde, M
Abstract : Babies below 37 weeks gestation now account for 9–12% of all births, and babies < 32 weeks gestation for 1–2%. Survival is also rising, and the expectation of life-long health. Preterm babies appear to be at substantially greater risk of features of the metabolic syndrome. For example it is estimated that currently 1 in 15 newly diagnosed hypertensives will have been born preterm. Early nutrition is the likely candiate mediator of long-term effects as well as a potential attenuator of aberrant trajectories of metabolic health. We will summarise research addressing childhood and adult metabolic health following preterm birth, the evidence that early nutrition and preterm growth affects risk for the metabolic syndrome. We will discuss methodological aspects of establishing causal relationships between infant feeding and later health outcomes, the pros and cons of observational versus randomized trials, practical issues in conducting infant nutrition studies/trials and performing long-term follow-up studies. We will provide an overview of the wide range of non-invasive technologies available for the identification of biomarkers in infants (including metabolomic technologies (using multi-component NMR/GCMS/LCMS platforms), genetic analyses using buccal swabs, and in vivo magnetic resonance imaging and spectroscopy to measure metabolites in the liver and brain.